2017
DOI: 10.15407/econindustry2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of innovation development of railway transport in Ukraine: financial aspects

Abstract: a>
Language: Russian

Abstract:
The research objects of the article are the financial aspects of innovation development of railway transport. Now the railway transport in Ukraine is in a state of deep crisis, which led to significant deterioration in the state of the production capacity of the branch reducing its transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors identified the following obstacles for the digital transformation of forestry industry [1][2][3][4][5]:  Industry monopolization.  Outdated regulatory framework principles.…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified the following obstacles for the digital transformation of forestry industry [1][2][3][4][5]:  Industry monopolization.  Outdated regulatory framework principles.…”
Section: Introductionmentioning
confidence: 99%